Evaluation of the performance of selective M-MIP to tetracycline using electrochemical and HPLC-UV method - Pizan-Aquino, Charles; Wong, Ademar [UNESP]; Avilés-Félix, Luis; Khan, Sabir [UNESP]; Picasso, Gino; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2020)
The purpose of this work was to evaluate the performance of selective M-MIP to tetracycline using electrochemical and HPLC-UV method. In this specific case, the model used was magnetic nanoparticles coated with MIP selective to tetracycline. The magnetic nanoparticles were obtained by a co-precipitation method using the precursor salts FeCl3·6H2O and FeCl2·4H2O, and were then modified with tetraethylorthosilicate and trimethoxysilyl propyl methacrylate. Finally, polymerization of the MIP resulted in a core@shell material. The structural and morphological characteristics of the synthesized polymers were determined by Fourier transform infrared spectrometry, transmission electron microscopy, scanning electron microscopy, vibrating sample magnetometry, and N2-sorption measurements analysis. The efficiency of the polymers was evaluated in binding experiments, using a reference chromatographic method for comparison with the tetracycline-selective sensor. The two techniques gave very similar results, with the adsorption of tetracycline on the M-MIP always being greater than on the counterpart M-NIP (magnetic non-imprinted polymer). An imprinting factor of 3.5 was obtained for the polymer synthesized with acrylic acid as functional monomer. Among the adsorption models evaluated, the Langmuir isotherm was most suitable for data analysis, with similar fits obtained for the two techniques. The applicability of M-MIP was confirmed using the electrochemical sensor and the reference HPLC-UV technique in commercial milk samples. The adsorption values obtained in these experiments were near 100%.
Keywords: core@shell material; Electrochemical sensor; HPLC-UV; Magnetic-MIP; Selective adsorption